Analisis Biaya Modal Usaha Terhadap Laba Perusahaan: Studi Kasus pada Pet Shop di Kota Gorontalo - Valentina Monoarfa; Atsiilah Suryani Batara; Diah Ayu Sinta; Haura Syifa Ilmi; Jessie Berliana Chelsea Manopo; Mohammad Zulkarnaen Chairul Usman; Muhammad Hidayat Nurwahid (Masyarakat Ekonomi Syariah Bogor, 2025)
This research aims to analyze the effect of business capital on company profits, with a focus on the pet shop business in Gorontalo City. Business capital has an important role in pet shop business operations, including providing stock, technology, infrastructure and human resource management. Effective capital management can improve service quality, expand marketing and optimize operations, which ultimately has an impact on increasing profits. This research uses a qualitative descriptive approach through in-depth interviews with pet shop owners and managers in Gorontalo City, such as Cleo Pet Shop, Garfield Pet Shop, and Mori Pet Shop. The research results show that the capital spent ranges from IDR 40,000,000 - IDR 50,000,000, and the greater the capital available, the greater the opportunity to gain significant profits. However, other factors such as selling price, service, product promotion and business location also have a big influence on company profits. Location strategy, appropriate marketing strategy, and good service can increase consumer appeal, which has an impact on sales volume and profitability. The results of this research conclude that proper business capital management, balanced with good marketing strategies and strategic location selection, can increase company profits, even though there are competitive factors.